Podophyllotoxin Exposure Affects Organelle Distribution and Functions in Mouse Oocyte Meiosis - Lu, Ping-Shuang; Xie, Lan-Ping; Kong, Xiao-Han; Xu, Yi; Sun, Shao-Chen (Frontiers in Cell and Developmental Biology, 2021)
Podophyllotoxin (POD) is one of the most characterized lignans which is commonly found in podophyllum, and its preparations and derivatives are widely used in the clinical treatment due to strong anti-tumor and anti-virus activities. POD has been reported for its neurotoxicity, respiratory and potential reproductive toxicity. In present study, we investigated the effects of POD on the organelles of mouse oocytes during meiosis. Our results showed that exposure to POD significantly reduced the developmental competence of mouse oocytes. Further analysis revealed that endoplasmic reticulum failed to accumulate to the spindle periphery, suggesting that POD exposure might affect protein synthesis during oocyte meiotic maturation. Similarly, abnormal Golgi apparatus distribution was found after POD exposure, which could be confirmed by the aberrant localization of Rab11a-related vesicles, indicating that POD induced vesicle-based protein transport disorder. We also found the aberrant accumulation of lysosomes in the cytoplasm of POD-exposed oocytes, which implied that POD might lead to aberrant protein degradation. Moreover, the perinuclear distribution of mitochondria was also significantly disturbed, indicating the mitochondrial dysfunction after POD exposure. In all, our study illustrated that exposure to POD might disrupt protein synthesis, transport, degradation and ATP production by its effects on the distribution and functions of organelles during mouse oocyte meiotic maturation.